Retraction: Development and validation of a brief form of the nursing questionnaire on organizational health - Vitale, Elsa; Caputo, Maria; Canonico, Anna (Acta Biomedica Atenei Parmensis, 2021)
THIS ARTICLE HAS BEEN RETRACTED Background and Aim of the work. Nurses underline the importance of implementing organizational and managerial practice through observance of standard procedures and that this system acts as a guarantor for himself and for the patients themselves. On the contrary, an unsafe environment determines high levels of stress among the staff that will inevitably affect users. This study aimed to validate a short version of the QISO, so that it can be more easily applied in the workplace and nurses, already struggling with the multiple activities, can respond quickly, outlining an easy photograph and above all fast of their working environment. Methods. The QISO questionnaire has been administered to nurses who work in the hospital, both surgical, medical and outpatient setting. To the same interviewers were asked to fill in the QISOsv later. Results. Cronbach’s α of the QISOsv is .878. The cut off value was also calculated for the reduced version which turns out to be 2.25. No significant differences existed between the two version in their results. Conclusions. The results obtained showed that the nurses interviewed were satisfied with their organizational context.